2001
DOI: 10.1007/pl00011101
|View full text |Cite
|
Sign up to set email alerts
|

The two-dimensional t-t'-U model as a minimal model for cuprate materials

Abstract: The addition to the Hubbard Hamiltonian of a t' diagonal hopping term, which is considered to be material dependent for high-T c cuprate superconductors, is generally suggested to obtain a model capable to describe the physics of high-T c cuprate materials. In this line of thinking, the two-dimensional t-t'-U model has been studied by means of the Composite Operator Method, which allows to determine the dynamics in a fully self-consistent way by use of symmetry requirements, as the ones coming from the Pauli p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
(101 reference statements)
0
12
0
Order By: Relevance
“…The formalism is based on two main ideas: (i) use of propagators of relevant composite operators as building blocks for any subsequent approximate calculations and (ii) use of algebra constraints to fix the representation of the relevant propagators in order to properly preserve algebraic and symmetry properties; these constraints will also determine the unknown parameters appearing in the formulation due to the noncanonical algebra satisfied by the composite operators. In the last fifteen years, COM has been applied to several models and materials: Hubbard [36][37][38][39][40][41][42][43][44][45][46][47], - [48][49][50][51], - [52], -- [53][54][55], extended Hubbard ( --) [56,57], Kondo [58], Anderson [59,60], two-orbital Hubbard [61][62][63], Ising [64,65], 1 − 1.2. Underdoped Cuprates.…”
Section: Introductionmentioning
confidence: 99%
“…The formalism is based on two main ideas: (i) use of propagators of relevant composite operators as building blocks for any subsequent approximate calculations and (ii) use of algebra constraints to fix the representation of the relevant propagators in order to properly preserve algebraic and symmetry properties; these constraints will also determine the unknown parameters appearing in the formulation due to the noncanonical algebra satisfied by the composite operators. In the last fifteen years, COM has been applied to several models and materials: Hubbard [36][37][38][39][40][41][42][43][44][45][46][47], - [48][49][50][51], - [52], -- [53][54][55], extended Hubbard ( --) [56,57], Kondo [58], Anderson [59,60], two-orbital Hubbard [61][62][63], Ising [64,65], 1 − 1.2. Underdoped Cuprates.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding calculations are reported in Ref. 33 where is shown that these two channels do not carry any new unknown ZFC. The self-consistence scheme closes; by considering the four channels (i.e., fermionic, spin-charge, pair and double occupancy-charge) we can set up a system of coupled selfconsistent equations for all the parameters.…”
Section: A the Two-site Hubbard Modelmentioning
confidence: 97%
“…where the summation range only over two sites at distance a from each other and the rest of notation is standard 33 . The hopping matrix t ij is defined by…”
Section: A the Two-site Hubbard Modelmentioning
confidence: 99%
“…In 2D, various extended HMs (EHMs) have been proposed as key models to explain the mechanisms for unconventional superconductivity in cuprates 16,[19][20][21] . The variety of phenomena predicted in the EHMs in 2D ranges from d-wave superconductivity and spin-/chargedensity waves to antiferromagnetism, ferromagnetism, and Mott metal-insulator transition at commensurate fillings 16,[18][19][20][21]27,[33][34][35] . However, even in 1D, the EHMs present an unexpected richness of properties.…”
Section: Introductionmentioning
confidence: 99%